Coping With Stress and Burnout Associated With Telecommunication and Online Learning - Mheidly, Nour; Fares, Mohamad Y.; Fares, Jawad (Frontiers in Public Health, 2020)
The COVID-19 pandemic substantially impacted the field of telecommunication. It increased the use of media applications that enable teleconferencing, telecommuting, online learning, and social relations. Prolonged time facing screens, tablets, and smart devices increases stress and anxiety. Mental health stressors associated with telecommunication can add to other stressors related to quarantine time and lockdown to eventually lead to exhaustion and burnout. In this review, the effects of the COVID-19 pandemic on communication and education are explored. In addition, the relationship between prolonged exposure to digital devices and mental health is studied. Finally, coping strategies are offered to help relieve the tele-burdens of pandemics.